Homeostatic generative design process: Emergence of the adaptive architectural form and skin to excessive solar radiation. (September 2021) - Showkatbakhsh, Milad; Kaviani, Saam
Natural organisms through their evolutionary developments, acquire adaptive morphological and behavioural characteristics within their environmental contexts. Through homeostatic behaviours, organisms, individually and collectively, will sustain internal and external equilibrium in face of environmental fluctuations. There is a wide range of morphological and behavioural traits across multiple species that are rooted in their homeostatic mechanisms throughout their lives. This paper presents an evolutionary design workflow with embedded homeostatic principles to generate a building cluster that is adapted to the contexts with extreme solar radiation.